Um modelo de interconexão de componentes para ambientes mulitmídia distribuídos - Silva, Carlos Eduardo da (2007)
Multimedia systems must incorporate middleware concepts in order to abstract hardware and operational systems issues. Applications in those systems may be executed in different kinds of platforms, and their components need to communicate with each other. In this context, it is needed the definition of specific communication mechanisms for the transmission of information flow. This work presents a interconnection component model for distributed multimedia environments, and its implementation details. The model offers specific communication mechanisms for transmission of information flow between software components considering the Cosmos framework requirements in order to support component dynamic reconfiguration